112 What does an out of hours consultant led palliative care advisory service look like?. (14th March 2023) - Fox, Hannah; Hall, Paula; Healey, Charlotte; Laird, Barry; Makin, Matt; Willis, Derek
Abstract : Background: Supportive Care UK provides a nationwide remote palliative consultant led service to support medical professionals. This study aimed to characterise the nature of calls made to their out of hours (OOH) helpline. Methods: Retrospective review of 126 anonymised call logs, documenting second on call phone advice given across 19 sites during OOH periods between January and September 2021. Data was collected on demographics of the call, the patient and the nature and complexity of advice. Results: 68% (86) calls were made on Saturdays and Sundays. Peak call times were 11–12 am and 5–6pm. The most common caller was a junior doctor (32), followed by staff grade doctors (19). 73% of callers were doctors (92), 13% (7) were clinical nurse specialists/advance nurse practitioners and 10% (12) were registered nurses. Patients were most frequently aged between 60 and 89 (61%). 78% (98) of patients had a malignant diagnosis, most commonly colorectal, urological and lung cancer. The commonest reason for calling was for advice regarding symptom control (58% – 73 calls). 18% (23) were regarding medical emergencies, 16% (20) about medication advice, 3% (4) about non-symptom control end of life care issues, 1.5% (2) regarding ethical advice. 14 calls (11%) were simple not requiring specialist palliative care knowledge. 96 calls (76%) were more complex including advice on symptom control and syringe driver adjustments. The remaining 16 calls (13%) were particularly complex requiring experienced specialist input, such as advice on Methadone, Ketamine, Phenobarbital and complex ethical discussions or decision making. Conclusions: This project demonstrates a pattern of usage of a second on call advice line across multiple sites nationwide. The most common usage of the service were training grade or staff grade doctors doctors calling predominantly for symptom advice, in the weekend day period about patients with a malignant diagnosis. Further analysis is ongoing.